Impact of Brown Adipose Tissue Reduction and Overfeeding on Adiposity and Depotspecific Adipose Tissue Cellularity: Brown Fat Reduction and Adipose Tissue Cellularity - Tulp, Orien L (European Journal of Applied Sciences, 2025)
Brown adipose tissue contributes to adaptive changes in metabolic energy expenditure in response to alterations in diet and environmental conditions, thereby assisting an animal to maintain thermoregulation and energy balance in various mammalian species including man and animals. Cafeteria overfeeding of normally lean rats during early postweaning growth typically results in significant hyperplasia and in an increased capacity non-shivering thermogenesis and energy expenditure in brown adipose tissue (BAT). The Interscapular BAT depot is readily surgically accessible and normally represents approximately one third of the total BAT mass in lean Sprague Dawley (SD) rats. The effects of experimental overnutrition via offering a Cafeteria feeding regimen (Café) combined with surgical reduction of the IBAT mass of adipose tissue cellularity and regional fat deposition was determined in lean SD rats during 8 weeks of postweaning growth and development to adulthood. Groups (n= 8 rats/group) of male, SD rats were fed a Purina Chow diet or the Chow diet plus the Café regimen for 52 days from weaning. An additional group of the Chow+Café regimen were subjected to surgical removal of their IBAT at 4 weeks of age and continued on the Chow+Café thereafter (Café-IBAT). At 80 days of age, measures of adiposity including anthropometrics and the mass and adipocyte cellularity in principle abdominal and subcutaneous fat depots were determined. Body weight (BW) and mid-abdominal girth were 20% greater in Café and Café-IBAT, while linear growth was similar in all groups. The mass of all fat depots was greater in Café fed animals (p=<0.05) and increased further in subcutaneous depots and total WAT accumulation in the Café IBAT animals (p=<0.05). Adipocyte lipid content and cell diameter of Café > controls in all depots with further increases in abdominal depots with Café-IBAT. Adipocyte number per WAT depots of Café > Control in all depots, with further increases in the Inguinal SC depot. Thus, these results are consistent with regional differences in the effects of Café feeding on postweaning adipose tissue hyperplasia, hypertrophy and depot mass and which underwent additional depot-specific differentiation in Café-IBAT. In conclusion, Café resulted in adipocyte hypertrophy in all depots studied, but the partial reduction of BAT mass in Cafe-IBAT rats resulted in only modest additional impact on overall adiposity during overfeeding, with the greatest impact in the ING SC depot, and thereby consistent with potential thermogenic compensation in other BAT depots to partially minimize the overall impact of the Café overfeeding regimen on developing adiposity in this strain.